Kajian Literatur: Faktor-Faktor Penentu Keberhasilan Implementasi Smart City di Negara Berkembang - Mukhamad Rizky Akbar; Maulana Firjatullah (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The smart city concept has emerged as a primary solution to address various global urbanization challenges. However, its implementation in developing countries frequently encounters unique obstacles, such as limited infrastructure, constrained budgets, and varying levels of community readiness. This study aims to identify and analyze the critical success factors for smart city implementation in developing nations using a literature review approach. The research employs a Systematic Literature Review (SLR) method, adapting the PRISMA guidelines. Data collection was conducted by screening scientific articles from leading academic databases published over the last five years. The review results indicate that the success of a smart city in developing contexts does not rely solely on technological advancement. There are four primary dimensions acting as determinants: (1) the governance dimension, encompassing regulatory support and bureaucratic transparency; (2) the technological infrastructure dimension, involving equitable internet access and centralized data integration; (3) the human resources dimension, focusing on the digital literacy of citizens and government apparatus; and (4) the financial dimension, which includes innovative financing models and public-private partnerships. The conclusion of this review emphasizes that cross-sector collaboration and strong leadership commitment remain the most crucial foundations. These findings are expected to provide a strategic reference framework for local governments in designing more sustainable and targeted smart city roadmaps.